Proteomic Identification of an Upregulated Isoform of Annexin A3 in the Spinal Cords of Rats in a Neuropathic Pain Model - Zou, Wangyuan; Xu, Wei; Song, Zongbin; Zhong, Tao; Weng, Yingqi; Huang, Changsheng; Li, Maoyu; Zhang, Chuanlei; Zhan, Xianquan; Guo, Qulian (Frontiers in Neuroscience, 2017)
Neuropathic pain (NP) is induced by nerve damage or a disturbance in the peripheral or central nervous systems. Nerve damage causes the activation of sensitizing mechanisms in the peripheral and central nervous systems, which induces transcriptional and post-transcriptional alterations in sensory nerves. However, the underlying mechanisms of NP remain elusive. In the study, Two-dimensional gel electrophoresis (2DGE)-based comparative proteomics identified 38 differential gel spots, and 15 differentially expressed protein (DEPs) between the sham and the chronic constriction injury (CCI) -induced neuropathic pain rats. Of them, Annexin A3 (ANXA3) was significantly increased after CCI with Western blot analysis and immunofluorescence imaging. A lentivirus delivering ANXA3 shRNA (LV-shANXA3) was administered intrathecally to determine the analgesic effects of ANXA3 on allodynia and hyperalgesia in a CCI-induced neuropathic pain model in rats. Further study showed that LV-shANXA3 reversed the upregulation of ANXA3, alleviated CCI-induced mechanical allodynia and thermal hyperalgesia. The study indicated that ANXA3 may play an important role in neuropathic pain.